Feasibility of extremely reduced-dose CT of the thoracic spine in human cadavers. (August 2020) - Weinrich, Julius Matthias; Warncke, Malte; Wiese, Nis; Regier, Marc; Tahir, Enver; Heinemann, Axel; Sehner, Susanne; Püschel, Klaus; Adam, Gerhard; Laqmani, Azien
Background: According to the as low as reasonably achievable (ALARA) principle, radiation exposure in computed tomography (CT) should be minimized while maintaining adequate image quality. Dedicated CT protocols combined with iterative reconstruction (IR) can reduce radiation dose and/or improve image quality. Purpose: To investigate the feasibility of extremely reduced-dose (RD) CT of the thoracic spine in human cadavers using a standard-dose (SD) and three different RDCT protocols reconstructed with filtered back projection (FBP) and IR. Material and Methods: The thoracic spines of 11 cadavers were examined using different RDCT protocols with decreasing reference tube currents (RDCT-1: 50 mAs; RDCT-2: 30 mAs; RDCT-3: 10 mAs) at 140 kV. A clinical SDCT (70 mAs, 140 kV) served as reference. Raw data were reconstructed using FBP and two increasing levels of IR (IRL4 and IRL6). Images were evaluated for image quality, diagnostic acceptability, and visibility of anatomical structures according to a 5-point-scale. Results: Regardless of the reconstruction technique, image quality was rated as diagnostically acceptable for all cadavers in SDCT and RDCT-1. Image quality of reconstructions with FBP were generally rated lower. Application of IR improved image quality ratings in SDCT and RDCT. RDCT-2 with IR was the most reduced-dose CT protocol which enabled diagnostically acceptable image quality in all cadavers. Compared to SDCT, RDCT protocols resulted in significantly reduced effective radiation doses (SDCT: 4.1 ± 1.5 mSv; RDCT-1: 2.9 ± 1.1 mSv; 2:1.7 ± 0.6 mSv; 3:0.6 ± 0.1 mSv; P  = 0.001). Conclusion: Diagnostically acceptable RDCT of the thoracic spine with 1.7 mSv is feasible using IR.